A polyethersulfone–bisphenol sulfuric acid hollow fiber ultrafiltration membrane fabricated by a reverse thermally induced phase separation process. Issue 14 (19th February 2018) - Liu, Sheng-Hui; Liu, Min; Xu, Zhen-Liang; Wei, Yong-Ming
Abstract : A novel antifouling polyethersulfone (PES) hollow fiber membrane was modified by the addition of bisphenol sulfuric acid (BPA-PS) using a reverse thermally induced phase separation (RTIPS) process. Abstract : A novel antifouling polyethersulfone (PES) hollow fiber membrane was modified by the addition of bisphenol sulfuric acid (BPA-PS) using a reverse thermally induced phase separation (RTIPS) process. BPA-PS was synthesized by click chemistry and was blended to improve the hydrophilicity of PES hollow fiber membranes. The performance of PES/BPA-PS hollow fiber membranes, prepared with different contents of BPA-PS and at different temperatures of the coagulation water bath, was characterized by scanning electron microscopy (SEM), pure water flux ( J w ), BSA rejection rate ( R ), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR) and water contact angle measurements. SEM morphologies revealed that a finger-like cross-section emerged in the hollow fiber membrane by a non-solvent induced phase separation (NIPS) mechanism while a sponge-like cross-section appeared in the hollow fiber membrane via the RTIPS method. Both FTIR and XPS analysis indicated that the sulfate group in BPA-PS was successfully blended with the PES membranes. The results from AFM and water contact angle measurements showed that the surface roughness increased and the hydrophilicity of the PES/BPA-PS hollow fiber membrane was improved with the addition of BPA-PS. The results demonstrated that the PES/BPA-PS membrane with 1 wt% BPA-PS via RTIPS exhibited optimal properties.